Go! With microsoft office 2003 brief (Prentice Hall, 2005)
For Introductory Computer courses in Microsoft Office 2003 or courses in Computer Concepts with a lab component for Microsoft Office 2003 applications. Teach the course YOU want in LESS TIME. The primary goal of the GO! Series is ease of implementation, with an approach that is based on clearly-defined projects for students and a one of a kind supplements package.